Facile preparation of Mn3O4 hollow microspheres via reduction of pentachloropyridine and their performance in lithium-ion batteries. Issue 14 (23rd January 2017) - Jiang, Zhan; Huang, Kaihua; Yang, Dian; Wang, Shuai; Zhong, Hong; Jiang, Chongwen
Abstract : H2 gas bubble-templating method synthesize Mn3 O4 hollow microspheres via a green synthesis of 2, 3, 5, 6-tetrachloropyridine reduced from pentachloropyridine by manganese. Abstract : Mn3 O4 hollow microspheres have been facilely prepared via a green synthesis of 2, 3, 5, 6-tetrachloropyridine reduced from pentachloropyridine by manganese. The specific hollow microspheres were made by a H2 gas bubble-templating method presenting a high specific surface area (87.1 m 2 g −1 ) and a big total pore volume (0.2030 cm 3 g −1 ). The Mn3 O4 hollow microspheres as an anode material demonstrate a good electrochemical performance, with a high reversible capacity of 646.9 mA h g −1 after 240 cycles at a current density of 200 mA g −1 . The good cycling performance is attributed to numerous mesopores, high specific surface area and big total pore volume, which can offer good electrical contact and conductivity as well as accommodate the mechanism strains. In addition, the yield and selectivity of 2, 3, 5, 6-tetrachloropyridine achieved up to 99.2% and 99.5%, respectively.